2018
DOI: 10.1136/thoraxjnl-2017-211439
|View full text |Cite
|
Sign up to set email alerts
|

Administration of mesenchymal stem cells during ECMO results in a rapid decline in oxygenator performance

Abstract: Mesenchymal stem cells (MSCs) have attracted attention as a potential therapy for Acute Respiratory Distress Syndrome (ARDS). At the same time, the use of extracorporeal membrane oxygenation (ECMO) has increased among patients with severe ARDS. To date, early clinical trials of MSCs in ARDS have excluded patients supported by ECMO. Here we provide evidence from an model of ECMO to suggest that the intravascular administration of MSCs during ECMO may adversely impact the function of a membrane oxygenator. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…1). The anti-inflammatory effects of MSCs have been mostly attributed to their release of paracrine factors, because of low engraftment of donorderived MSCs into at the host lung tissue after MSC therapy (Qin et al, 2012;Millar et al, 2019). In support of this, MSCconditioned media have been suggested to reduce pro-inflammatory mediator levels and inflammatory cell counts in ARDS models (Ionescu et al, 2012;Goolaerts et al, 2014;Chen et al, 2015;Su et al, 2019;Xu et al, 2019).…”
Section: Induction Of Anti-inflammatory Responsementioning
confidence: 99%
“…1). The anti-inflammatory effects of MSCs have been mostly attributed to their release of paracrine factors, because of low engraftment of donorderived MSCs into at the host lung tissue after MSC therapy (Qin et al, 2012;Millar et al, 2019). In support of this, MSCconditioned media have been suggested to reduce pro-inflammatory mediator levels and inflammatory cell counts in ARDS models (Ionescu et al, 2012;Goolaerts et al, 2014;Chen et al, 2015;Su et al, 2019;Xu et al, 2019).…”
Section: Induction Of Anti-inflammatory Responsementioning
confidence: 99%
“…Importantly, ECMO has become an increasingly common therapeutic modality for patients with severe ARDS (Bellani et al 2016;Papazian et al 2019). In an ex vivo model, MSCs administered intravascularly were found to adhere to membrane oxygenator fibers during ECMO, resulting in a significant reduction of flow through the circuit (Millar et al 2019). Further investigations should be performed with alternative routes of administration, such as intrabronchial, to identify which would be a viable option for this clinical situation.…”
Section: Clinical Trials Of Msc Therapy In Patients With Ardsmentioning
confidence: 99%
“…However, the application of MSC in patients treated with ECMO needs further thorough clinical investigation. Recently, Millar et al demonstrated a rapid decline in oxygenator performance in an ex-vivo model of ECMO [41]. Another group evaluated the viability and activity of MSC in ex vivo circulation conditions with and without an oxygenator [42].…”
Section: Discussionmentioning
confidence: 99%